Representation, attribution, and purification: a study on the dissemination of competitive sports public opinion in the digital media environment - Yang, Yan; Zhang, Yueting; Shi, Bing (Frontiers in Sociology, 2025)
Taking the dissemination of competitive sports public opinion in the digital media environment as the research object, this study adopts case analysis, phenomenology, narrative evaluation, and logical induction to examine the phenomenon from the perspective of communication characteristics. It rationally analyzes the manifestations and causes of communication misconduct and proposes purification strategies to promote the high-quality dissemination of competitive sports public opinion culture. The study finds that the phenomenological essence of competitive sports public opinion dissemination under digital media is characterized by an “information dividend” resulting from explosive growth, which accelerates the transformation of athletes into internet celebrities. Symbolic communication enhances the visibility of competitive sports-related public opinion while simultaneously encouraging the proliferation of peripheral behavioral subcultures. Interactive marketing-driven dissemination contributes to the precise identification and recommendation of market needs. However, this also gives rise to issues such as online public safety risks, forced negative intervention in athletes’ daily life, training, and competitions, as well as the chaotic and uncontrollable spread of public opinion. Drawing on Actor-Network Theory (ANT), this study constructs a tripartite attribution framework—actor, translation, and network—to explain the causes of misconduct. These include athletes’ personal expression, role-playing needs, and self-presentation desires; public idol worship; the rise of digital consumer culture; and increasing societal demand for sports public figures. To purify the public opinion environment, the study proposes a comprehensive approach based on moral constitutional governance, emotional guidance, and collaborative governance. This involves strengthening moral and legal systems governing online discourse, enhancing the guiding and regulatory role of mainstream media, and constructing a collaborative governance mechanism involving multiple communication actors.